A Review of Inflammatory Markers in Metabolic Syndrome: Life Sciences-Medicine - kumari, Dr.T.M.J.Santhosha; Dr.G.Revathy; Dr.Prabha (International Journal of Life Science and Pharma Research, 2023)
The conditions included in the definition of metabolic syndrome typically include central obesity (excessive fat accumulation around the waist), insulin resistance, hyperglycemia (elevated blood sugar levels), dyslipidemia (abnormal levels of lipids in the blood), and hypertension (high blood pressure). Having any three or more of these conditions is considered to be indicative of metabolic syndrome. Metabolic syndrome (MetS) is emerging as a major public health problem with pro-inflammatory changes leading to Insulin Resistance and Cardiovascular Disease (CVD) at a very young age. Metabolic syndrome (MetS) is a global health concern; metabolic syndrome is becoming more common in our country. It is found to be a risk factor for insulin resistance and abnormal adipose tissue . Clinical symptoms of the syndrome could include abdominal obesity, hypertension, diabetes, hypertriglyceridemia, and low HDL cholesterol. So far various studies have been conducted on the effect of inflammatory markers like Serum Uric acid (UA), serum homocysteine, Leptin, Lp(a) etc. Most of them have reported a positive correlation between these inflammatory markers and the various components of (MetS) like abdominal obesity, elevated Blood pressure, Fasting blood Glucose and Lipid profile abnormalities like elevated Triglycerides (TAG) and low High Density Lipoprotein-Cholesterol (HDL-C). Various studies have reported a positive correlation between serum uric acid and Serum Homocysteine and Lp(a) in causing endothelial dysfunction and premature Cardiovascular events. Hence a review of the studies pertaining to the various inflammatory markers was done. There was an association of various inflammatory markers like uric acid, homocysteine, MDA, lipoprotein and others. More awareness must be created even at the high school level regarding the ill effects of sedentary lifestyle the likely hood of metabolic syndrome. An early identification of surging biomarker levels in high-risk children may find new cases at an earlier stage to prevent upcoming diabetes mellitus and its complications.